Development of a new scale to measure subjective career success: A mixed‐methods study. (11th August 2015) - Shockley, Kristen M.; Ureksoy, Heather; Rodopman, Ozgun Burcu; Poteat, Laura F.; Dullaghan, Timothy Ryan
Summary: Career success is a main focus of career scholars as well as organizational stakeholders. Historically, career success has been conceptualized and measured in an objective manner, mainly as salary, rank, or number of promotions. However, the changing nature of work has also necessitated a change in the way many employees view success, adding a more subjective component. Although there has been theoretical discussion and calls to develop a comprehensive measure of subjective career success, no contemporary comprehensive quantitative measure exists. The goal of this study was to create and validate a measure of subjective career success, titled the Subjective Career Success Inventory (SCSI). The SCSI includes 24 items that address subjective career success via eight dimensions. The scale was developed and validated through four phases of data collection, beginning with interviews and focus groups, followed by item sorting tasks, then item refinement through confirmatory factor analysis, and finally convergent and discriminant validity quantitative analysis. Theoretical and practical implications are discussed. Copyright © 2015 John Wiley & Sons, Ltd.